Turbo Gradient and Spin Echo PROPELLER-Diffusion Weighted Imaging for Orbital Tumors: A Comparative Study With Readout-Segmented Echo-Planar Imaging - Fu, Qing; Kong, Xiang-chuang; Liu, Ding-Xi; Zhou, Kun; Guo, Yi-hao; Lei, Zi-Qiao; Zheng, Chuan-sheng; Yang, Fan (Frontiers in Neuroscience, 2021)
Purpose: To qualitatively and quantitatively compare the image quality and diagnostic performance of turbo gradient and spin echo PROPELLER diffusion-weighted imaging (TGSE-PROPELLER-DWI) vs. readout-segmented echo-planar imaging (rs-EPI) in the evaluation of orbital tumors. Materials and methods: A total of 43 patients with suspected orbital tumors were enrolled to perform the two DWIs with comparable spatial resolution on 3T. The overall image qualities, geometric distortions, susceptibility artifacts and lesion conspicuities were scored by using a 4-point scale (1, poor; 4, excellent). Quantitative measurements, including contrast-to-noise ratios (CNRs), apparent diffusion coefficients (ADCs), geometric distortion rates (GDRs) and lesion sizes were calculated and compared. The two ADCs for differentiating malignant from benign orbital tumors were evaluated. Wilcoxon signed-rank test, Kappa statistic and Receiver operating characteristics (ROC) curves were used. Results: TGSE-PROPELLER-DWI performed superior in all subjective scores and quantitative GDR evaluation than rs-EPI (p<0.001), and excellent interobserver agreement was obtained for Kappa value ranging 0.876~1.000. ADClesion of TGSE-PROPELLER-DWI was significantly higher than those of rs-EPI (p<0.001). Mean ADC of malignant tumors was significantly lower than that of benign tumors both in two DWIs. However, the AUC for differentiating malignant and benign tumors showed no significant difference in the two DWIs (0.860 vs 0.854, p=0.7448). Sensitivity and specificity could achieve 92.86% and 72.73% for TGSE-PROPELLER-DWI with a cutoff value of 1.23 x10-3mm2/s, and 85.71% and 81.82% for rs-EPI with a cutoff value of 0.99 x10-3mm2/s. Conclusion: Compared with rs-EPI, TGSE-PROPELLER-DWI showed minimized geometric distortion and susceptibility artifacts significantly improved the image quality for orbital tumors, and achieved comparable diagnostic performance in differentiating malignant and benign orbital tumors.